2017
DOI: 10.1007/s00280-017-3444-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of retreatment with nivolumab in metastatic melanoma patients previously treated with nivolumab

Abstract: This study showed that retreatment with nivolumab is an option for select metastatic melanoma patients after previous nivolumab treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
44
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 20 publications
5
44
1
5
Order By: Relevance
“…A previous report suggests that the response to initial ICI treatments correlates with the clinical response to ICI rechallenge treatment in patients with melanoma [30]. However, our results failed to indicate a relationship between clinical outcomes of initial ICI treatment and ICI rechallenge treatment in patients with NSCLC.…”
Section: Discussioncontrasting
confidence: 99%
“…A previous report suggests that the response to initial ICI treatments correlates with the clinical response to ICI rechallenge treatment in patients with melanoma [30]. However, our results failed to indicate a relationship between clinical outcomes of initial ICI treatment and ICI rechallenge treatment in patients with NSCLC.…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, in one of the PR patients, the metastases were decreased with nivolumab re-administration. Although the underlying mechanism is not clear, Nomura et al 20 reported that two melanoma patients with PD on both the first-line nivolumab and second-line ipilimumab achieved PR in the third-line nivolumab retreatment. In some sequential cases, the immune status may be altered in response to ipilimumab treatment.…”
Section: Discussionmentioning
confidence: 99%
“…(nivolumab) and anti-CTLA-4 (ipilimumab) has shown positive results in tumor treatment and significant enhancement in patients with metastatic melanoma [36], advanced RCC [37], and metastatic CRC [16,38] [40]. Based on conditional survival analysis of first-line treatment, Shao [41] showed that patients with advanced RCC put on nivolumab plus ipilimumab therapy had high survival rate compared with sunitinib.…”
Section: Discussionmentioning
confidence: 99%